Pulmonary Artery Catheter Monitoring in Patients with Cardiogenic Shock: Time for a Reappraisal? - Maurizio Bertaina; Alessandro Galluzzo; Nuccia Morici; Alice Sacco; Fabrizio Oliva; Serafina Valente; Fabrizio D’Ascenzo; Simone Frea; Pierluigi Sbarra; Elisabetta Petitti; Silvia Brach Prever; Giacomo Boccuzzi; et al. (Cardiac Failure Review)
Cardiogenic shock represents one of the most dramatic scenarios to deal with in intensive cardiology care and is burdened by substantial short-term mortality. An integrated approach, including timely diagnosis and phenotyping, along with a well-established shock team and management protocol, may improve survival. The use of the Swan-Ganz catheter could play a pivotal role in various phases of cardiogenic shock management, encompassing diagnosis and haemodynamic characterisation to treatment selection, titration and weaning. Moreover, it is essential in the evaluation of patients who might be candidates for long-term heart-replacement strategies. This review provides a historical background on the use of the Swan-Ganz catheter in the intensive care unit and an analysis of the available evidence in terms of potential prognostic implications in this setting.